(untitled) (Literary Voice, 2024)
Good bodily and mental health is a condition of well-being. We may keep our bodies in good health by embarking on a quest to explore the deepest corners of our minds. The practical and scientific approaches for comprehending the relationship between the mind and body are the main emphasis of the study. Through their writings, Deepak Chopra and Swami Vivekananda emphasize the vitality of the fountain known as consciousness as a prelude to awareness, focus, and purpose - all of which are subsequently incorporated into medical procedures like radiation, chemotherapy, and surgery. Both the writers’ literary works highlight and discuss ancient Indian life sciences like Yoga and Ayurveda as well as Western Medicine. Through the field of Medical Humanities, the intersection of Literature, Philosophy, and Medical Science, this research will engage significant elements required for the purpose. Thus, the research delves into both the physiological and psychological facets of preserving bodily health.